2003
DOI: 10.1177/073724770302800304
|View full text |Cite
|
Sign up to set email alerts
|

Identifying an Indicator of Growth in Early Writing Proficiency for Elementary School Students

Abstract: In this study we compared alternative measures of early writing performance to identify an indicator of writing proficiency that teachers could use to monitor student growth and evaluate instructional effectiveness. The participants were 15 second-grade students in a summer school program for students at risk. The performance sampled was word copying, sentence copying, word dictation, and sentence dictation. Two-to three-minute samples of performance were obtained and several different scores were examined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(109 citation statements)
references
References 10 publications
(20 reference statements)
4
103
0
Order By: Relevance
“…Fuchs, Fuchs, Hosp, & Hamlett, 2003) may provide richer information about students' reading skills based on oral-reading fluency than what has been supplied previously. In addition, researchers continue to enlarge the domain for CBM content to include secondary material (e.g., Busch & Espin, 2003;Espin & Tindal, 1998), early writing (e.g., Lembke, Deno, & Hall, 2003), early reading (L.S. Fuchs, Fuchs, & Compton, 2004), and phonics skills (e.g., Stecker, 2000).…”
Section: Future Directionsmentioning
confidence: 98%
“…Fuchs, Fuchs, Hosp, & Hamlett, 2003) may provide richer information about students' reading skills based on oral-reading fluency than what has been supplied previously. In addition, researchers continue to enlarge the domain for CBM content to include secondary material (e.g., Busch & Espin, 2003;Espin & Tindal, 1998), early writing (e.g., Lembke, Deno, & Hall, 2003), early reading (L.S. Fuchs, Fuchs, & Compton, 2004), and phonics skills (e.g., Stecker, 2000).…”
Section: Future Directionsmentioning
confidence: 98%
“…Anytime a student stopped writing he or she was prompted once to continue. Brief 5-minute writing tasks have been used extensively in prior writing research (Berninger et al, 1996;Connelly, Dockrell, Walter, & Critten, 2012;Graham et al, 1997;Kent, Wanzek, Petscher, Al Otaiba, & Kim, 2014), including curriculum-based measurement research (Espin et al, 2000), with proven validity (Dockrell, Connelly, Walter, & Critten, 2015;Lembke, Deno, & Hall, 2003). To control for potential prompt effects, half of the classes wrote the essay without planning to the prompt "Do you think teachers should give students homework every days?"…”
Section: Methodsmentioning
confidence: 99%
“…Research on these measures is summarized below. Lembke et al (2003) administered copying and dictation tasks to 15 at-risk second graders and scored their responses for WW, WSC, CWS, and correct letter sequences (CLS). They also obtained 5-minute written responses to a story prompt and scored the average number of WW, WSC, CWS, and correct minus incorrect word sequences (CIWS).…”
Section: Stage 1: Technical Features Of the Static Scorementioning
confidence: 99%
“…We first compared traditional CBM approaches in writing (i.e., story prompts) to word-and sentence-writing measures developed for beginning writers (McMaster et al, 2009; sample measures can be found at http://progressmonitoring.org). We adapted Word and Sentence Copying tasks from Lembke et al (2003) and administered these, along with traditional story prompts, to 50 first graders. We also developed Letter, PictureWord, and Picture-Theme prompts, all designed to promote generation of words, sentences, and stories.…”
Section: Measures Incorporating Transcription and Ideationmentioning
confidence: 99%
See 1 more Smart Citation